The Communication in Mentoring Activities Victims of Sexual Violence in West Sumatera - Vanisya, Winda; Roem, Elva Ronaning; Sarmiati (Komunika, 2025)
Inequality in the treatment of victims of sexual violence can be seen in those who do not have friends who talk about feelings of confusion, fear, and a lack of knowledge about what to do after an act of sexual violence occurs. This research discusses the communication activities of companions at Nurani Perempuan with victims of sexual violence in West Sumatra. This research aims to analyze communication activities by Nurani Perempuan Women’s Crisis Center as a companion to victims of sexual violence in West Sumatra. This research uses a case study research approach with research data collection methods by conducting observations, in-depth interviews with companions of victims of sexual violence at Nurani Perempuan, and documentation. The research results show that communication between one victim and another victim is very unique. In order to achieve good communication, the companion must be able to build the victim's trust so that they want to talk about their case. So that the companion who is initially active in asking questions will become a listener to the victim's story until the mentoring process is complete and the victim begins to improve.